Influence of school principal leadership and organizational culture on teacher performance with work motivation as a moderating variable - Minarseh, Minarseh; Rahmawati, Rahmawati; Zakaria, Nurman (Junal Ilmu Manajemen, 2024)
National education has an important role in a country to create students who are intelligent, qualified, creative, independent and have character. Through education, students can gain knowledge, skills, values and other behavioral patterns to support life success and continue their existence. This research was conducted at SMP Negeri 9 Pinggir with the aim of finding out the influence between the principal's leadership and organizational culture on teacher performance with work motivation as a moderating variable. The population in this study was 31 teachers and the sample was determined using a saturated census technique so that the total sample in this study was 31 respondents. The data analysis technique uses Structural Equation Modeling (SEM) using SmartPLS version 3.0 software. The results of the research show that the principal's leadership has a significant direct influence on teacher work motivation, organizational culture has a significant direct influence on teacher work motivation, the principal's leadership has a significant direct influence on teacher performance, organizational culture has a significant direct influence on teacher performance, work motivation has a significant direct effect on teacher performance, principal leadership has a significant indirect effect on teacher performance through work motivation, organizational culture has a significant indirect effect on teacher performance through work motivation